Posthumanism and feminist theology in selected texts of octavia butler / Elham Mohammadi Achachelooei - Elham Mohammadi , Achachelooei (2016)
This thesis applies Daphne Hampson‘s ―post-Biblical‖ as well as Rosemary Radford Ruether‘s ecofeminist ―Biblical‖ perspectives on four selected texts by Octavia Butler. They are Parable of the Sower, Parable of the Talents, ―Amnesty,‖ and ―The Book of Martha.‖ In this research, I try to offer new theological readings to these stories to show how Butler‘s postmodern theological stand reflects an optimistic view about the spiritual potential of humanity to establish a more promising, that is to say peaceful, life on Earth. The study is concerned with the relationship between God, human beings, and nature, and tries to reveal Butler‘s mastery in constructing an inclusive approach of life or coexistence on Earth. This study also deals with what Hampson and Ruether recognize as the Othering tendency in Christianity which seems to hierarchically subjugate human beings and nature under the dominance of an Almighty God. Hampson and Ruether discuss how this Othering aspect, which appears in rigid interpretations of the Bible, could be replaced by new theological understandings which recognize egalitarianism as the true pattern in the triangle of God, human beings, and nature. My research focuses especially on the characterization of the protagonists in these selected stories by Butler; stories which are examples of postmodern science fiction. It reveals how, unlike in traditional forms of science fiction, Butler‘s heroines are not prefixed within the usual racial and sexual characteristics in science fiction as white and belonging to the masculine gender. In other words, this study tries to reveal the capacity of science fiction to, parallel with the innovative theological perspective of the stories, embody a ―literature of change,‖ as advocated by critics of science fiction.